KELAS PRENATAL YOGA MENGATASI NYERI PUNGGUNG DAN KRAM: PERSEPSI IBU HAMIL TRIMESTER 3 - ., Kudarti; Widhayanti, Ratna (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Prenatal yoga is useful for dealing with discomfort especially in the final trimester. The 3rd trimester discomfort most often complained of by pregnant women associated with physical complaints include back pain and cramps. The purpose of this study is to determine the perceptions of third trimester pregnant women who take prenatal yoga classes in reducing complaints of back pain and cramps. The design of this study used a case study qualitative study at Budi Luhur Kudus Clinic. Subjects in this study were pregnant women who had attended a prenatal yoga class of 5 people who routinely followed at least 3 times at gestational age above 28 weeks. Trainers or instructors who are always the same and have basic prenatal yoga training are very helpful for pregnant women in taking prenatal yoga. This is because trainers can pay attention to movements and poses which may or may not be carried out by pregnant women while taking yoga classes. The results of this study indicate that pregnant women who take prenatal yoga classes can reduce complaints that often occur in pregnant women in the third trimester such as stiffness in the waist and back and cramps. Breathing exercises in prenatal yoga can also reduce shortness of breath. Conclusions in this study that pregnant women who take prenatal yoga classes regularly can reduce complaints of pegel, back pain and cramps that are often experienced by mothers in pregnancy in the third trimester. Keywords: Prenatal Yoga, Back Pain, Cramps, Pregnancy Trimester 3